Radiation protection infrastructure—challenges in developing countries. (19th August 2021) - Adhikari, Kanchan P; Boersma, Hielke Freerk; Coates, Roger; Coulor, Whitney; Gallego, Eduardo; Ben Omrane, Latifa; Cruz Suarez, Rodolfo; Tsegmed, Uranchimeg
Abstract: A special session was held in the International Radiation Protection Association (IRPA15) Congress to address the particular challenges facing developing countries regarding radiation protection infrastructure. The objective was to identify and share the key challenges facing developing countries regarding the ability to introduce and establish effective radiation protection programmes. The experiences of key international organisations (International Atomic Energy Agency, Pan American Health Organisation and World Health Organisation) that have support programmes were discussed, along with a perspective from several countries with developing programmes. The key common challenges include: governmental commitment at senior levels, with provision of the necessary resources: establishment of an independent regulatory body and related infrastructure: appropriate numbers of qualified staff in all necessary fields, including their education and training: supporting physical infrastructure, such as dosimetry and measurement equipment including calibration laboratories. In addressing these challenges the importance of support from the key international organisations was emphasised. More emphasis should be given to the application of the graded approach. The establishment of support networks at a national or regional level that allow for the sharing of experiences and resources, and that support the wellbeing of isolated professionals, is also crucial. In this aspect the support from wider professional bodies such as IRPA and established national radiation protection societies can also play a key role.